Audit committee financial expertise and audit report lag: Malaysia further insight - Zalailah Salleh; Baatwah, Saeed Rabea; Norsiah Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2017)
Recent audit and financial reporting quality research suggest that audit committee financial expertise is a crucial ingredient for high quality financial reports. However, Malaysian literature has reported no association between audit committee financial expertise and audit report timeliness. Using audit report lag, we examined whether Malaysian audit committee financial expertise is relevant for financial reporting timeliness. Using data from 2005 to 2011 from the top 100 Malaysian companies and the fixed effects panel data approach, we find that audit committee financial expertise is not significantly associated with audit report lag proxies. We further examined this issue with the basic premise that audit committee independence enhances the role of audit committee financial expertise. However, the interaction between these mechanisms shows an insignificant association. Additional investigation reveals that these results are driven by the lack of independence on Malaysian boards. We also find evidence suggesting that neither a large number of subsidiaries nor the quality of financial reporting sufficiently justify the recent Malaysian reforms relating to the financial reporting timeframe.